"Eye-Black" Sign Secondary to Nivolumab Immunotherapy. (March 2020) - Priya, Sarv; Graham, Michael
Abstract : Abstract: A 54-year-old woman with known chest wall melanoma (post–wide local excision) presented for imaging after a yearlong therapy with nivolumab. 18 F-FDG PET/CT was performed 1 day after she completed the immunotherapy. Maximum intensity projection images showed bilateral relatively symmetrical uptake in the facial region. On fused PET/CT images, the uptake was seen corresponding to subcutaneous malar prominence underneath the orbits (like eye-black stripe used in sports) with subcutaneous malar calcification. Repeat PET/CT performed after 3 months revealed significant decrease in the malar uptake. Interval resolution of the uptake likely suggested this being inflammatory and secondary to immunotherapy.